(untitled) (Global Journal of Human-Social Science, 2017)
Biodiversity is the essence and manifestation of evolutionary history of life on earth and species is the most conspicous form of the biodiversity. Ungulates are the hoofed mammalian species of vertebrates. Exploration of Rakchham-Chhitkul Wildlife Sanctuary present in the Baspa (Sangla) valley, district Kinnaur in Himachal Pradesh, India revealed the presence of three species of wild ungulates, belonging to three genera and two Families Moschidae and Bovidae of Order Artiodactyla. It was further observed that no wild member of Order Perissodactyla was present in the study area. It was found that the Bharal or Blue Sheep is the most populous ungulate in the sanctuary area.